(untitled) (Basel Institute on Governance Policy Briefs, 2017)
This policy brief summarises the main findings and lessons learned from research on corruption, social norms and behaviours in Tanzania. While the findings show that petty corruption is prevalent and results in inequitable public service delivery, they also inform that citizen and public officials’ attitudes and behaviours towards corruption are shifting as a result of changes in the political environment. The evidence furthermore suggests that the effectiveness of conventional anti-corruption approaches may be enhanced by incorporating behavioural insights about entrenched social norms and collective understandings that are associated with practices of bribery and favouritism.